Pengaruh Kecerdasan Emosional Terhadap Kinerja Usaha Dengan Konflik Peran Ganda Sebagai Variabel Intervening (Studi Kasus Pada Pelaku Usaha Mikro Kecamatan Tanjung Selor) - Adelia Januarti; Dewi Qomariah Imelda; Nurus Soimah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study was to determine whether Emotional Intelligence, on Business Performance with Dual Role Conflict of women micro business actors in Tanjung Selor. The type of research method used is quantitative. The population in this study were female micro business actors in Tanjung Selor. The number of respondents studied was 120 respondents. The results of this study are first, it was found that there is a relationship between Emotional Intelligence on Dual Role Conflict has a negative effect insignificant, the relationship between Emotional Intelligence on Business Performance has a positive effect insignificant, and the relationship between Dual Role Conflict on Business Performance has a positive effect insignificant.